2011
DOI: 10.1097/mou.0b013e32834bb783
|View full text |Cite
|
Sign up to set email alerts
|

Robotic approaches for male infertility and chronic orchialgia microsurgery

Abstract: Long-term prospective controlled trials are necessary to assess the true benefit for robotic-assisted microsurgery. The preliminary findings are promising, but further evaluation is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 35 publications
(24 reference statements)
0
27
0
1
Order By: Relevance
“…Early studies in animal model 34,35 using LIVE demonstrated a 100% patency rate. The group from Parekattil et al 36,37 has reported one of the earliest series of human robotic microsurgical VE. Using again LIVE, Parekettil et al 36,37 reported a significant decrease in the operating time with the robot (mean 120 min; range 50-180 min) compared to the non-robotic microsurgical method (150 min; range 120-240 min).…”
Section: Robotic-assisted Microsurgical Vementioning
confidence: 99%
See 3 more Smart Citations
“…Early studies in animal model 34,35 using LIVE demonstrated a 100% patency rate. The group from Parekattil et al 36,37 has reported one of the earliest series of human robotic microsurgical VE. Using again LIVE, Parekettil et al 36,37 reported a significant decrease in the operating time with the robot (mean 120 min; range 50-180 min) compared to the non-robotic microsurgical method (150 min; range 120-240 min).…”
Section: Robotic-assisted Microsurgical Vementioning
confidence: 99%
“…The group from Parekattil et al 36,37 has reported one of the earliest series of human robotic microsurgical VE. Using again LIVE, Parekettil et al 36,37 reported a significant decrease in the operating time with the robot (mean 120 min; range 50-180 min) compared to the non-robotic microsurgical method (150 min; range 120-240 min). They also reported an earlier return of sperm with the robotic technique compared to the non-robotic method, although the postoperative total motile sperm counts of the two methods were not significantly different.…”
Section: Robotic-assisted Microsurgical Vementioning
confidence: 99%
See 2 more Smart Citations
“…In 2008, our group introduced the use of robotic assistance for targeted microsurgical denervation of the spermatic cord (RMDSC) for patients with chronic groin or testicular pain. 9,10 The initial inertia in the use of robotics in microsurgery has primarily been a lack of access to the robot by microsurgeons and the 10-fold increase in cost of the equipment in comparison to standard microsurgical equipment. However, our group has recently published a larger volume study comparing robotic to pure microsurgical vasectomy reversal and have shown that with increased volume, enhanced surgical efficiency, eliminated need for a skilled microsurgical assistant, and decreased operative time, these procedure can be performed at a cost similar to or even less than standard microsurgical procedures.…”
Section: Introduction and Historical Perspectivementioning
confidence: 99%